Factors Associated With Potential Progressive Course of Primary Biliary Cholangitis: Data From Real-world US Database. Issue 9 (October 2019) - Younossi, Zobair M.; Stepanova, Maria; Golabi, Pegah; Epstein, Robert S.; Strauss, Marcie E.; Nader, Fatema; Racila, Andrei
Abstract : Background and Aims: Although relatively, primary biliary cholangitis (PBC) is an important cause of nonalcoholic chronic liver disease which may lead to liver transplantation. PBC patients with alkaline phosphatase (ALP) ≥1.5× the upper limit of normal (ULN) tend to have a more aggressive course. The study was designed to identify factors associated with ALP≥1.5×ULN or cirrhosis in PBC and to evaluate concomitant health care resource utilization. Methods: We used a large real-world database that contained comprehensive and continuous electronic medical recored/claims data from over 500 health care practices or systems from the United States. Results: Of 195 million patients included in the database, 36, 317 were adults with PBC. After applying exclusion criteria, 15, 875 patients comprised the final PBC cohort (63.0±13.5 y, 78% female, 71% privately insured, 5% covered by Medicaid, 57% with other autoimmune diseases, 46% with cirrhosis); 6083 (38%) had ALP≥1.5×ULN. Patients with ALP≥1.5×ULN were more frequently female, less covered by Medicaid, had more pruritus, cirrhosis, and other autoimmune diseases ( P <0.05). In multivariate analysis, older age, female gender, the presence of other autoimmune diseases, and having compensated or decompensated cirrhosis were independently associated with having ALP≥1.5×ULN in PBC ( P <0.05). In contrast, being male was associated with higher risk of cirrhosis in PBC [odds ratio 2.3 (95% confidence interval, 2.1-2.5)]. Patients with ALP≥1.5×ULN and/or with cirrhosis also incurred substantially more health care resource utilization ( P <0.05). Conclusions: Many clinical, sociodemographic, and economic factors are associated with a potentially more aggressive profile of PBC with elevated ALP. These data may inform clinicians to implement management strategies to optimize care of these patients. Abstract : Supplemental Digital Content is available in the text.